Charter and Ordinances of the City of Waterbury, Connecticut, with Amendments Thereto 230, § 6 (1902) - (:unkn) unknown (My University, 1897)
Good Order and Decency, § 6: Prohibited the possession of any steel, iron, or brass knuckles, or slung shot or weapon of similar character. Also prohibited the concealed carry of any weapon. Violators shall forfeit the weapon and pay a fine of not less than five nor more than one hundred dollars for each offense.
Keywords: CARRY - CONCEALED; POSSESSION